Improved Sample Preparation Methodology on Lime Mortar for Reliable 14C Dating - Ortega, Luis Angel; Zuluaga, Maria Cruz; Alonso-Olazabal, Ainhoa; Insausti, Maite; Murelaga, Xabier; Ibañez, Alex (IntechOpen, 2012)
None